1991
DOI: 10.1107/s0108767391003550
|View full text |Cite
|
Sign up to set email alerts
|

Electron diffraction structure analysis of diketopiperazine – a direct phase determination

Abstract: Three-dimensional electron-diffraction intensity data from crystalline textures of diketopiperazine (2,5-0108-7673/91/050510-06503.00 piperazinedione) published by B. K. Vainshtein in 1955 [Zh. Fiz. Kim. (1955 are found to be suitable for ab initio structure analysis via conventional direct phase determination based on the © 1991 International Union of Crystallography DOUGLAS L. DORSET 511 estimates of three-and four-phase structure invariants. Of the 289 non-zero reflections found in this data set, 196 with [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In another recent study substituted DKP has been demonstrated to form self-assembled supramolecular "tapes" of two different classes depending on the planarity or nonplanarity of the DKP ring. 5 Structural investigations on crystals of DKP by X-ray [6][7][8] and electron diffraction 9 showed that the eight heavy atoms are essentially coplanar. Sletten 10 found by X-ray diffraction that trans-dimethylDKP [the cyclic dipeptide from D-alanine with L-alanine] deviates slightly from ring planarity into a chair configuration with the methyls axial while cis-dimethylDKP [from L-alanine with L-alanine] is appreciably puckered into a twisted boat conformation with the methyls axial.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study substituted DKP has been demonstrated to form self-assembled supramolecular "tapes" of two different classes depending on the planarity or nonplanarity of the DKP ring. 5 Structural investigations on crystals of DKP by X-ray [6][7][8] and electron diffraction 9 showed that the eight heavy atoms are essentially coplanar. Sletten 10 found by X-ray diffraction that trans-dimethylDKP [the cyclic dipeptide from D-alanine with L-alanine] deviates slightly from ring planarity into a chair configuration with the methyls axial while cis-dimethylDKP [from L-alanine with L-alanine] is appreciably puckered into a twisted boat conformation with the methyls axial.…”
Section: Introductionmentioning
confidence: 99%
“…An impactful portion of this dogma-busting work was conducted by Dorset, who embarked on a quest to apply direct methods to electron-diffraction amplitudes originally recorded at ∼50 kV by Vainshtein, Zvyagin, and other pioneering electron crystallographers in the 1950s. Because these ED data were collected prior to the advent of ab initio phasing, Vainshtein and co-workers usually relied on pairing experimental ED amplitudes with phases borrowed from corresponding X-ray structures. Naturally, this approach invited concerns regarding phase bias.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…(Indeed, even maps computed from unit structure factors with the correct phases will, in general, reveal the crystal structure for small molecules.) However, Dorset (1991b) solved the structure ab initio using symbolic addition, and found the positions of all the non-hydrogen atoms without recourse to the X-ray result, and the data are now used as a test case for those developing phasing methods.…”
Section: Examples Organic Moleculesmentioning
confidence: 99%